The Effect of Internal Communication on the Performance of Educational Personnel at the Cirebon Maritime Academy - Siagian, Fereddy (Universitas Malikussaleh, 2021)
The purpose of this study is to find out and analyze the effect of internal communication on the performance of educational staff. This type of research uses descriptive and quantitative research. The population in this study amounted to 102 people, using the Slovin formula obtained a sample of 51 people with a simple random sampling technique. The testing instrument uses a validity test and a reliability test. While the data analysis technique used is a simple regression analysis with the t test and the coefficient of determination test. From the results of the research data obtained values for internal communication variables of (9,852) > (2,011) with a sig value of 0,000 < from the value of 0.05. Meanwhile for the R Square value obtained a result of 0.669, meaning that the change in the performance of the teaching staff at the Cirebon AMC Educational Institution was 66.9% influenced by internal communication while the remaining 33.1% was caused by other variables not examined. The conclusion of this study is that internal communication greatly influences the performance of educational staff in the work environment of the Cirebon AMC Educational Institution. good to better demonstrate the success of the Cirebon Maritime Academic Educational Institute.